Antimicrobial resistance profile of non-aureus Staphylococci isolates from buffalo, goat and sheep mastitis in the Northeast region of Brazil. Issue 3 (7th August 2020) - Santos, André de Souza; Lima, Débora Costa Viegas de; Abad, Atzel Candido Acosta; Oliveira, Pollyanne Raysa Fernandes de; Silva, José Givanildo da; Moura, Guilherme Santana de; Silva, Amanda Thaís Ferreira; Amorim, Vinícius da Silva; Costa, Mateus Matiuzzi da; Mota, Rinaldo Aparecido
Abstract: The study described in this Research Communication investigated the genotypic and phenotypic profiles of resistance to beta-lactams and other antimicrobials in non-aureus Staphylococci (NAS) isolated from buffalo, goat and sheep mastitis in the Northeast region of Brazil. A total of 190 isolates were analyzed and 42.3, 43.9 and 23.6% of them were positive for blaZ gene in buffalo, goat and sheep, respectively. Regarding the animal groups, in goats, amoxicillin was the antimicrobial with highest resistance index (72.7%), followed by penicillin G in buffaloes (51.9%) and ampicillin in sheep (43.1%). With regard to multiple antimicrobial resistance, 30.8% of NAS isolates from buffalo milk samples, 25.8% from goats and 25.0% from sheep presented multidrug-resistance. In the minimum inhibitory concentration (MIC) technique, amoxicillin MIC50 and MIC90 were 64 and 128 μg/ml, respectively, among isolates of the three animal species. In conclusion, high rates of resistance to beta-lactams are presented among NAS isolated from mastitis cases in buffaloes, goats and sheep in Northeast region of Brazil. These results provide an alert to animal and human health researchers, suggesting that the frequency of NAS needs to be reduced because they carry resistance genes which might increase the existing levels of antimicrobial resistance.